A simple sign for recognizing off-axis OCT measurement beam placement in the context of multicentre studies. - Lisanne J Balk (Public Library of Science (PLoS), 2012)
Purpose Optical coherence tomography (OCT) allows quantification of the thickness of the retinal nerve fibre layer (RNFL) thickness, a potential biomarker for neurodegeneration. The estimated annual RNFL loss in multiple sclerosis amounts to 2 μm using time domain OCT. The recognition of measurement artifacts exceeding this limit is relevant for the successful use of OCT as a secondary outcome measure in clinical trials. Methods Prospective study design. An exploratory pilot study (ring and volume scans) followed by a cohort study (1,980 OCT ring scans). The OCT measurement beam was placed off-axis to the left, right, top and bottom of the subjects pupil and RNFL thickness of these scans were compared to the centrally placed reference scans. Results Off-axis placement of the OCT measurement beam resulted in significant artifacts in RNFL thickness measurements (95%CI 9μm, maximal size of error 42μm). Off-axis placement gave characteristic patterns of the OCT live images which are not necessarily saved for review. Off-axis placement also causes regional inhomogeneity of reflectivity in the outer nuclear (ONL) and outer plexiform layers (OPL) which remains visible on scans saved for review. Conclusion Off-axis beam placement introduces measurement artifacts at a magnitude which may mask recognition of RNFL loss due to neurodegeneration in multiple sclerosis. The resulting pattern in the OCT live image can only be recognised by the technician capturing the scans. Once the averaged scans have been aligned this pattern is lost. Retrospective identification of this artifact is however possible by presence of regional inhomogeneity of ONL/OPL reflectivity. This simple and robust sign may be considered for quality control criteria in the setting of multicentre OCT studies. The practical advice of this study is to keep the OCT image in the acquisition window horizontally aligned whenever possible.